Lateral organ boundaries 1 is a disease susceptibility gene for citrus bacterial canker disease - Hu, Yang; Zhang, Junli; Jia, Hongge; Sosso, Davide; Li, Ting; Frommer, Wolf B.; Yang, Bing; White, Frank F.; Wang, Nian; Jones, Jeffrey B. (My University, 2014)
Citrus bacterial canker (CBC) disease occurs worldwide and incurs considerable costs both from control measures and yield losses. Bacteria that cause CBC require one of six known type III transcription activator-like (TAL) effector genes for the characteristic pustule formation at the site of infection. Here, we show that Xanthomonas citri subspecies citri strain Xcc306, with the type III TAL effector gene pthA4 or with the distinct yet biologically equivalent gene pthAw from strain XccA[superscript w], induces two host genes, CsLOB1 and CsSWEET1, in a TAL effector-dependent manner. CsLOB1 is a member of the Lateral Organ Boundaries (LOB) gene family of transcription factors, and CsSWEET1 is a homolog of the SWEET sugar transporter and rice disease susceptibility gene. Both TAL effectors drive expression of CsLOB1 and CsSWEET1 promoter reporter gene fusions when coexpressed in citrus or Nicotiana benthamiana. Artificially designed TAL effectors directed to sequences in the CsLOB1 promoter region, but not the CsSWEET1 promoter, promoted pustule formation and higher bacterial leaf populations. Three additional distinct TAL effector genes, pthA*, pthB, and pthC, also direct pustule formation and expression of CsLOB1. Unlike pthA4 and pthAw, pthB and pthC do not promote the expression of CsSWEET1. CsLOB1 expression was associated with the expression of genes associated with cell expansion. The results indicate that CBC-inciting species of Xanthomonas exploit a single host disease susceptibility gene by altering the expression of an otherwise developmentally regulated gene using any one of a diverse set of TAL effector genes in the pathogen populations.
Citation: Hu, Y., Zhang, J., Jia, H., Sosso, D., Li, T., Frommer, W. B., … Jones, J. B. (2014). Lateral organ boundaries 1 is a disease susceptibility gene for citrus bacterial canker disease. Retrieved from http://krex.ksu.edu
Keywords: Citrus bacterial canker; Xanthomonas citri